Psychiatric disorders and future violent arrests : a prospective study among detained girls - Colins, Olivier (2020)
This study scrutinizes if detained girls with psychiatric disorders were at risk for future violent arrests during adolescence. A structured diagnostic interview was performed to determine the presence of various psychiatric disorders in 313 detained girls. Official juvenile arrest records were collected. With three exceptions that are in need of replication, psychiatric disorders (e.g., post-traumatic stress disorder, subtypes of conduct disorder), psychiatric disorder categories (e.g., anxiety disorders), and psychiatric comorbidity patterns were not prospectively related to future violent arrests. Our findings suggest that detained girls with psychiatric disorders should not be considered more dangerous than their counterparts without disorders, at least not during adolescence